Yes,I mean first we write :
$f_{X_1+X_2}=\int_{\mathbb{R}}f_{X_1}(t)f_{X_2}(z-t)\, dt\\ =\int_{-\infty}^{-1}f_{X_1}(t)f_{X_2}(z-t)\, dt+\int_{-1}^1f_{X_1}(t)f_{X_2}(z-t)\, dt+\int_{1}^{+\infty}f_{X_1}(t)f_{X_2}(z-t)\, dt\\ =\int_{-\infty}^{-1}0\cdot f_{X_2}(z-t)\, dt+\int_{-1}^1f_{X_1}(t)f_{X_2}(z-t)\, dt+\int_{1}^{+\infty}0\cdot f_{X_2}(z-t)\, dt\\ =\int_{-1}^1f_{X_1}(t)f_{X_2}(z-t)\, dt\\ =\int_{-1}^1\frac{1}{2}f_{X_2}(z-t)\, dt\\ =\frac{1}{2}\cdot \int_{-1}^1f_{X_2}(z-t)\, dt$
and now we consider the intervals for $z$ , right? We have to write this last integral as a sum of integrals as…